2016
DOI: 10.1088/1755-1315/44/5/052022
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Crystal Violet on Activated Carbon Prepared from Coal Flotation Concentrate

Abstract: Abstract. The objective of this study is firstly to investigate the floatability properties of ZilanVan coal after microwave irradiation and secondly to produce activated carbon from flotation concentrate in order to remove Crystal Violet (CV) from waste water. The flotation experiments showed that microwave heating at 0.9 kW power level for 60 sec exposure time enhanced the hydrophobicity and increased the flotation yield. The activated carbon with remarkable surface area (696 m 2 /g) was produced from the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…This result is consistent with the literature. Most adsorption studies of crystal violet and methyl blue dyes have been reported to fit well with the Langmuir isotherm model [10,20,21].…”
Section: Discussionmentioning
confidence: 91%
“…This result is consistent with the literature. Most adsorption studies of crystal violet and methyl blue dyes have been reported to fit well with the Langmuir isotherm model [10,20,21].…”
Section: Discussionmentioning
confidence: 91%